Curriculum Development Strategies in Five Countries: The United States, Finland, Japan, Singapore, and Indonesia - Marhamah Marhamah; Dizza Awwana; Gadis Ayu Safitri; Nurhafiza Dzikrina Salma; Puan Nayla Khairani (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
The curriculum is a key component of the education system, serving as a guideline for the learning process. Every nation has a unique approach to curriculum development that is based on cultural values, national needs, and objectives for human resource development. The United States, Finland, Singapore, Japan, and Indonesia are the five nations whose curriculum development approaches are examined and contrasted in this article. Library research and the analysis of numerous pertinent literature sources are the methods employed. The study's findings show that while every nation takes a different approach, they all aim to strike a balance between students' character development, academic mastery, and 21st-century skills. This article aims to examine and compare curriculum development strategies in five countries: the United States, Finland, Singapore, Japan, and Indonesia. The method used is library research, analyzing various relevant literature sources. The results of the study indicate that although each country has a different approach, all strive to balance academic mastery, 21st-century skills, and student character development.